SALAFISME DI INDONESIA : IDEOLOGI, POLITIK NEGARA, DAN FRAGMENTASI - Krismono Krismono (Millah: Journal of Religious Studies, 2017)
Taking the focus of Salafism study in Indonesia, the article is intended to analyze the important shifts of the Salafi ideology in responding to regional and international political situations, particularly in relation to state policy which has resulted in a wide range of theological implications and pragmatism of the Salafi doctrine., The article also aims to place correctly about the existence of Salafi factions in Indonesia. Implementation of a non-monolithic Salafist ideology in Saudi Arabia has created a polemic and conflict that brought influence and resonated rapidly to the emergence of new forms of Salafism in Indonesia that not only used their approach to religion but also state ideology. Interestingly, fragmented Salafism in Indonesia into some of these factions initially began only from the doctrinal problems to spread into personal and even financial problems.